2017
DOI: 10.1103/physreve.95.022134
|View full text |Cite
|
Sign up to set email alerts
|

Eigenvector statistics of the product of Ginibre matrices

Abstract: We develop a method to calculate left-right eigenvector correlations of the product of m independent N × N complex Ginibre matrices. For illustration, we present explicit analytical results for the vector overlap for a couple of examples for small m and N . We conjecture that the integrated overlap between left and right eigenvectors is given by the formula O = 1 + (m/2)(N − 1) and support this conjecture by analytical and numerical calculations. We derive an analytical expression for the limiting correlation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 98 publications
(123 reference statements)
0
13
0
Order By: Relevance
“…Remarkably, the function O 1 (z) can be efficiently studied within the formalism of free probability [33] which recently allowed to extend the Chalker-Mehlig formulas to a broad class of invariant ensembles beyond the Gaussian case [3,37]. O 1 (z) is also known for a finite size of the complex Ginibre matrix [8,35] and products of small Ginibre matrices [7]. It has been recently shown that for complex Ginibre matrices the one-and two-point functions conditioned on an arbitrary number of eigenvalues are related to determinantal point processes [2].…”
Section: Gin2mentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the function O 1 (z) can be efficiently studied within the formalism of free probability [33] which recently allowed to extend the Chalker-Mehlig formulas to a broad class of invariant ensembles beyond the Gaussian case [3,37]. O 1 (z) is also known for a finite size of the complex Ginibre matrix [8,35] and products of small Ginibre matrices [7]. It has been recently shown that for complex Ginibre matrices the one-and two-point functions conditioned on an arbitrary number of eigenvalues are related to determinantal point processes [2].…”
Section: Gin2mentioning
confidence: 99%
“…First, we find convenient integral representations, which should allow the use of the Laplace method. For this we start from (39) and, using the integral representation for Hermite polynomials in (7) with both signs, we obtain…”
Section: Asymptotic Analysismentioning
confidence: 99%
“…However, when moving to products of m complex Ginibre ensembles the circular law is modified to 1 mπ |x| 2 m −2 on the unit disc. The resulting overlap is then multiplied by this density, with the quadratic power in (4.12) replaced by 2 → 2/m [14].…”
Section: Macroscopic Bulk Limit Of the Overlapsmentioning
confidence: 99%
“…Using a combination of Green's functions and diffusion equations, it was noticed early on that the Dysonian dynamics in this ensemble couples the complex eigenvalues and their eigenvectors in a non-trivial way [10,11]. These techniques were further developed including Feynman diagrams [12,13], free probability [14] or stochastic differential equations [15], and applied to different ensembles including products of elliptic Ginibre matrices [12]. These, as well as truncated unitary and spherical ensembles, were analysed in [16] using probabilistic means, after an earlier breakthrough for these methods in [17], see also [18] for the correlations between angles of eigenvectors.…”
Section: Introductionmentioning
confidence: 99%